Effect of government R&D subsidies on firms' innovation in China. Issue 1 (2nd January 2020) - Wu, Ruirui; Liu, Zhiying; Ma, Chaoliang; Chen, Xiafei
ABSTRACT: This study investigates the effects of R&D subsidies on firms' innovation using panel data of Chinese listed firms from 2008 to 2013. Through propensity score matching method, we determine that recurrent, high-tech firms are more likely to receive public grants. Moreover, firms affiliated with higher-level governments and located in minimally marketised regions have a higher probability of receiving government financial support. China's state intervention to correct market failure related to firms' R&D activity is confirmed to be reasonable in an observable time given an instantaneous additionality effect. However, the stimulation effect of R&D subsidies on innovation outputs has not been verified. Results obtained through a continuous matching method show no optimal amount of R&D subsidies for firms in China, but a declining yet a positive marginal effect of treatment has been identified given an increase in the amount of R&D subsidies.